Grand Canyon National Park - Denniston, Jennifer Rasin; Gleeson, Bridget (Lonely Planet Publications Pty Limited, 2016)
Lonely Planet Grand Canyon National Park is your passport to the most relevant, up-to-date advice on what to see and skip, and what hidden discoveries await you. Go rafting on the Colorado River, ride a mule down into the Grand Canyon, or view it from above on a helicopter ride around the canyon's rim; all with your trusted travel companion. Get to the heart of Grand Canyon National Park and begin your journey now! Inside the Lonely Planet Grand Canyon Travel Guide: User-friendly highlights and itineraries help you tailor your trip to your personal needs and interests. Insider tips to save time and money and get around like a local, avoiding crowds and trouble spots. Essential info at your fingertips-- hours of operation, phone numbers, websites, transit tips, prices, emergency information, park seasonality, hiking trail junctions, viewpoints, landscapes, elevations, distances, difficulty levels, and durations. Focused on the best-- hikes, drives, and cycling tours. Honest reviews for all budgets-- eating, sleeping, camping, sight-seeing, going out, shopping, summer and winter activities, and hidden gems that most guidebooks miss. Contextual insights give you a richer, more rewarding travel experience.